TINJAUAN PENGGUNAAN BEA METERAI DALAM SURAT PERJANJIAN - , Rini Yesti, S.H.; , Dwi Haryati, S.H., M.H ([Yogyakarta] : Universitas Gadjah Mada, 2012)
The research concerning the overview of use of stamp duty within letter of contract aims to observe the relationship between stamp duty use with letter of contract, the law effect of underpaid stamp duty and its fulfillment way, the law effect of stamp duty overdue within letter of contract and the notary position in term of involved controlling the implementation of the Stamp Duty Act. This research used normative juridical (doctrinal) approach was literature law research. The type of data used was secondary data consisted of primary, either secondary or tertiary law materials included literature study to books, law and regulation and research result in organized as scientific paper. The data collecting instruments used documentary study technique. Data obtained was analyzed qualitatively. Based on the research result it concluded that the relationship between stamp duty use with letter of contract was in term of tax and verification, because it arranged in the written form and used for indebted verification of stamp duty when the document had been completed. Therefore, the letter of contract as document has to meet the stamp duty requirements. The law effect of underpaid stamp duty was considered unsealed thus it unable to use as evidence instrument in the court. The settlement ways was by settling the indebted stamp duty and fine of 200 % (two hundred percents) from underpaid or unpaid stamp duty by stamping (nazegeling) through post office. The law effect of stamp duty overdue within letter of contract was released from stamp duty fulfill obligation and indebted administrative fine post to five years counted from date the document was arranged. Therefore, it has no need to implement the stamping (nazegeling) because the engagement to fulfill the stamp duty obligation was revoked by the presence of overdue. The notary position to control the implementation of the Stamp Duty Act was in term of controlling pay office income from stamp duty as general officer and its related to certificate as evidence instrument and would being charged the administrative sanction